Winter wheat growth, development and productivity depending on the intensification of cultivation technology under direct seeding on ordinary blackearth of the Stavropol territory - A. V. Gonochenko; R. G. Gadzhiumarov; A. N. Dzhandarov; V. K. Dridiger (Зерновое хозяйство России, 2025)
The current study was conducted with the purpose to identify the effect of technology intensity on crop formation and grain quality of winter wheat grown under direct seeding on ordinary blackearth in the Stavropol Territory. The work was carried out at the North Caucasus FSRC in 2020–2023, where winter wheat was cultivated after peas using extensive, normal and intensive technologies in crop rotation, such as peas – winter wheat – sunflower – winter wheat, in which the soil for all crops was not cultivated for three years before and during the trials. There has been found that the technologies did not have a significant impact on field germination and the period of sprout emergence. However, due to the better nutrition regime and less plant damage by diseases and pests, the largest above-ground mass (4095 g/m2 ), leaf surface (3.87 m2 /m2 ) and surface photosynthetic potential (2.37 million m2 × day/ha) were formed by winter wheat under intensive technology, which was reliably 32.1–33.9 % more than normal and 55.0–59.8 % more than under extensive technology. The largest winter wheat productivity was obtained under intensive technology with 6.26 t/ha, which was ensured by high density of plants, their productive tillering, grain content and grain weight per ear. Under normal and extensive technology, the productivity was significantly lower by 2.38 t/ha (38.0 %) and 4.98 t/ha (79.6 %), which was due to a significant decrease in all yield structure elements. Under extensive technology, the yielded grain was of 5 class, under normal and intensive technology it was food grain of 3 class.